2012
DOI: 10.1007/s00264-012-1676-5
|View full text |Cite
|
Sign up to set email alerts
|

Effect of callus development on the deformation of external fixation frames

Abstract: Purpose We designed a sensor that measures the bending moments at the articulations and the torque of the rod of a Hoffmann II® external fixation. We considered the effect of the callus formation in the stabilisation of a "fracture-fixation system." Methods Four Hoffmann II® frame configurations were mechanically tested. Two carbon fibre tubes represent the bone fragments (length 180 mm, outer diameter 25 mm, inner diameter 19 mm). The callus is represented by the interposition of springs of different rigidity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…This behaviour could be justified by the global stiffness variation of the external fixator. A smaller free pin span makes the whole structure stiffer than a larger one [29,30], and for any given regenerate stiffness of callus, a more flexible fixation tends to increase the ratio of the total load supported by the callus [31,32]. Nevertheless, the results of Figure 5, and Tables 3 and 4 show also that increasing the axial distance from 70 mm to 90 mm does not change load share ratios very much.…”
Section: Discussionmentioning
confidence: 90%
“…This behaviour could be justified by the global stiffness variation of the external fixator. A smaller free pin span makes the whole structure stiffer than a larger one [29,30], and for any given regenerate stiffness of callus, a more flexible fixation tends to increase the ratio of the total load supported by the callus [31,32]. Nevertheless, the results of Figure 5, and Tables 3 and 4 show also that increasing the axial distance from 70 mm to 90 mm does not change load share ratios very much.…”
Section: Discussionmentioning
confidence: 90%
“…To better understand such information and to reach an evidence level, the consequent next step is to build up a database. Distinct healing patterns for normal and aberrant courses of healing could be extracted and interpreted (Burny et al, 2012;Claes et al, 2002). Ideally, data collection should concentrate on human patients to increase the significance of results.…”
Section: Discussion and Outlookmentioning
confidence: 99%
“…A 20 mm gap was left at the fracture site and the bone callus was represented by springs of different rigidity: k 1 = 0 N/mm, k 2 = 0.153 N/mm and k 3 = 0.460 N/mm. We used springs with increasing rigidity to simulate increasing bone callus stiffness, while the values of springs were chosen to be feasible with benchtop tests and in accordance with previous works [ 13 ]. The behaviour of each component of the external fixator was assumed to be isotropic, linear, and homogenous, based on data provided by the datasheet [ 23 ], and according to similar studies observed in the literature [ 21 , 24 ].…”
Section: Methodsmentioning
confidence: 99%
“…In indirect measurement approaches, the strain of the implant is evaluated against the healing time. Since the deformation of the frame is inversely proportional to the callus stiffness, information on the state of the bone can be obtained by monitoring the level of deformation on the external fixator [ 13 ]. Only a few studies in the past have evaluated the displacement of the external fixator components as a mean for monitoring fracture healing.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation